Experimental Investigation of Hydrodynamic Cavitation Method's Operational Parameters for Removing Organic Pollutants from Water, Case Study: Methyl Orange Dye - Alireza Asaddokht; Abdollah Rashidi Mehrabadi; Mohammad Reza Jalili Ghazizadeh (آب و فاضلاب, 2024)
The entry of large volumes of industrial effluents containing organic pollutants and dyes into water has made pollution an important issue and led to more attention being paid to advanced oxidation processes for industrial wastewater treatment. Cavitation, due to its ability to produce active free radicals, is a technique that has been considered to increase the efficiency of water and wastewater treatment processes in order to remove organic chemical compounds and decompose pollutants resistant to biological decomposition. The purpose of this research is to use hydrodynamic cavitation to remove the methyl orange dye and optimize the operating parameters for color removal efficiency. For this purpose, cavitation was produced through the use of a pump and an orifice plate with a 4 mm diameter hole, and methyl orange with a concentration of 2 mg/L was tested at each stage. In the following, the effect of operating parameters, including pressure in the range of 0.5 to 6.5 bar, temperature in the range of 8 to 40 °C, pH in acidic, neutral, and alkaline conditions after 135 minutes was determined to achieve the maximum decolonization in optimal conditions. In this study, optimal conditions for achieving the highest removal efficiency (51.7%) were obtained at an inlet pressure of 5.5 bar and a cavitation number of about 0.14 (Ca≈0.14). The results of this investigation showed that the decomposition and removal of methyl orange dye using the hydrodynamic cavitation method is sensitive to the pH of the solution, especially in acidic conditions, which are more suitable conditions for the production of hydroxyl radicals than in alkaline conditions, and has higher efficiency in acidic conditions. Also, increasing the temperature of the solution due to the effect on the saturated vapor pressure will increase the decolonization rate.